Lake-depth related pattern of genetic and morphological diatom diversity in boreal Lake Bolshoe Toko, Eastern Siberia - Stoof-Leichsenring, Kathleen R. (Dr.); Dulias, Katharina; Biskaborn, Boris (Prof.); Pestryakova, Luidmila A. (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.) (PLOS ONE, 2020)
Large, old and heterogenous lake systems are valuable sources of biodiversity. The analysis of current spatial variability within such lakes increases our understanding of the origin and establishment of biodiversity. The environmental sensitivity and the high taxonomic richness of diatoms make them ideal organisms to investigate intra-lake variability. We investigated modern intra-lake diatom diversity in the large and old sub-arctic Lake Bolshoe Toko in Siberia. Our study uses diatom-specific metabarcoding, applying a short rbcL marker combined with next-generation sequencing and morphological identification to analyse the diatom diversity in modern sediment samples of 17 intra-lake sites. We analysed abundance-based compositional taxonomic diversity and generic phylogenetic diversity to investigate the relationship of diatom diversity changes with water depth. The two approaches show differences in taxonomic identification and alpha diversity, revealing a generally higher diversity with the genetic approach. With respect to beta diversity and ordination analyses, both approaches result in similar patterns. Water depth or related lake environmental conditions are significant factors influencing intra-lake diatom patterns, showing many significant negative correlations between alpha and beta diversity and water depth. Further, one near-shore and two lagoon lake sites characterized by low (0-10m) and medium (10-30m) water depth are unusual with unique taxonomic compositions. At deeper (>30m) water sites we identified strongest phylogenetic clustering in Aulacoseira, but generally much less in Staurosira, which supports that water depth is a strong environmental filter on the Aulacoseira communities. Our study demonstrates the utility of combining analyses of genetic and morphological as well as phylogenetic diversity to decipher compositional and generic phylogenetic patterns, which are relevant in understanding intra-lake heterogeneity as a source of biodiversity in the sub-arctic glacial Lake Bolshoe Toko.